Adsorption of Methylene Blue on Sewage Sludge Based Granular Activated Carbon - Liu, L.H.; Ai, H.N.; Lin, Y.; Liu, Y.Y.; He, Q. (Asian Journal of Chemistry, 2014)
In this study, sewage sludge based granular activated carbons used for adsorption of methylene blue were prepared using calcium sulphate as binder and activator. The effect of preparation conditions of activated carbons on methylene blue adsorption was investigated in detail. The optimized conditions were obtained with activation temperature 700 ºC, calcium sulphate and sludge mass ratio 30 % and activation time 1 h as well as a heating rate of 5 ºC/min. The sample prepared for adsorption of methylene blue under the optimized conditions was 71.94 mg/g. Nitrogen adsorption, scanning electron microscope (SEM) and Fourier transform infrared spectrum (FT-IR) were used to characterize the sample. The experimental results indicate that it is a typical mesoporous adsorbent. Many acidic groups and holes were found resulting from ablating on its surfaces. The activation mechanisms and reactions of calcium sulphate were similar to that of the combination of H2SO4 and KOH.